2017
DOI: 10.2147/cia.s146613
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing of psychotropic medication for nursing home residents with dementia: a general practitioner survey

Abstract: ObjectiveThe aim of this study was to identify factors influencing the prescribing of psychotropic medication by general practitioners (GPs) to nursing home residents with dementia.Subjects and methodsGPs with experience in nursing homes were recruited through professional body newsletter advertising, while 1,000 randomly selected GPs from southeastern Australia were invited to participate, along with a targeted group of GPs in Tasmania. An anonymous survey was used to collect GPs’ opinions.ResultsA lack of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 16 publications
4
42
0
Order By: Relevance
“…However, in some of the studies, participating GPs demonstrated a good knowledge of both non‐pharmacological and pharmacological management options in BPSD . For example, in one study, most GPs reported proactively reducing psychotropic medications and routinely recommending non‐pharmacological interventions prior to commencing medications; however, these GPs still felt they required “more training” in BPSD.…”
Section: Unmet Primary Care Needsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, in some of the studies, participating GPs demonstrated a good knowledge of both non‐pharmacological and pharmacological management options in BPSD . For example, in one study, most GPs reported proactively reducing psychotropic medications and routinely recommending non‐pharmacological interventions prior to commencing medications; however, these GPs still felt they required “more training” in BPSD.…”
Section: Unmet Primary Care Needsmentioning
confidence: 99%
“…In 4 studies, the prescribing of antipsychotics was seen to enable carers, nursing home staff, and the person with dementia to cope with BPSD: “ he was weeping for his wife who has been dead for many years … on quetiapine … the uncontrollable weeping had stopped. ” Although in some studies GPs were aware of the risks of antipsychotic prescribing in people with dementia, these risks were seen to relate to longevity of life whereas in BPSD “quality of life issues prevailed.” In several studies, GPs' believed antipsychotics positively impacted on the quality of life of people with BPSD . This contributed to their reluctance to discontinue antipsychotics .…”
Section: Justification Of Antipsychotic Prescribingmentioning
confidence: 99%
See 3 more Smart Citations